2014
DOI: 10.1093/infdis/jiu006
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Enteritidis Modulates Intestinal Epithelial miR-128 Levels to Decrease Macrophage Recruitment via Macrophage Colony-Stimulating Factor

Abstract: Salmonella can upregulate intestinal epithelial miR-128 expression, which, in turn, decreases levels of epithelial cell-secreted M-CSF and M-CSF-induced macrophage recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Recent studies have characterized deregulation of host miRNAs following infection with extracellular ( H. pylori ) (12), or intracellular ( Salmonella enterica ) (13), Gram-negative bacteria, as well as in the response to Gram-positive ( Listeria monocytogenes ) (14) and other pathogenic bacteria ( Mycobacterium (15) and Francisella species (16)).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have characterized deregulation of host miRNAs following infection with extracellular ( H. pylori ) (12), or intracellular ( Salmonella enterica ) (13), Gram-negative bacteria, as well as in the response to Gram-positive ( Listeria monocytogenes ) (14) and other pathogenic bacteria ( Mycobacterium (15) and Francisella species (16)).…”
Section: Introductionmentioning
confidence: 99%
“…31 In human in-testinal epithelial HT29 cells, miRNA-128 level was strongly increased by infection with Salmonella enterica serovar enteritidis, and delivery of antimiRNA-128 antagomir into mice significantly increased macrophage recruitment and suppressed Salmonella infection. 32 These results suggest that miRNA-128 is involved in inflammatory response, and upregulation of miRNA-128 may reduce inflammatory responses. Nevertheless, to the best of the authors' knowledge, there has been no research that focused on the role of miRNA-128 in periodontitis or periodontopathogenassociated immune responses.…”
Section: Discussionmentioning
confidence: 90%
“…In mononuclear cells from Alzheimer disease, miRNA‐128 upregulation is suggested as the reason for the reduced amount of lysosomal cathepsins, and miRNA‐128 inhibition in monocytes improved amyloid β(1‐42) degrading ability 31 . In human intestinal epithelial HT29 cells, miRNA‐128 level was strongly increased by infection with Salmonella enterica serovar enteritidis , and delivery of antimiRNA‐128 antagomir into mice significantly increased macrophage recruitment and suppressed Salmonella infection 32 . These results suggest that miRNA‐128 is involved in inflammatory response, and upregulation of miRNA‐128 may reduce inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cimino et al [ 60 ] reported M-CSF is a direct target of miR-148b. Wang et al [ 61 ] identified M-CSF as a target gene of miR-214, and Zhang et al [ 62 ] reported M-CSF as a target of miR-128. The present study found miR-26a regulates M-CSF expression and recruitment of macrophages.…”
Section: Discussionmentioning
confidence: 99%